An epic example narration and scholarship of the Humadapnon Sugidanon - Aguinaldo, Dennis Andrew S. (UP Los Baños Journal, 2008)
The folk epic formally represents the aesthetic height of precolonial literature in the Philippines, the longest period in our literary history. Despite this, there is a dearth of scholarship on the subject. The paper traces the contours of these gaps, especially those concerned with narration. It then executes hermeneutically grounded readings of the main characters of the longest Filipino epic ever encountered, the Humadapnon Sugidanon. In the process, it marks possible territory for the revival of the epic in current literary teaching and practice. It then projects the study toward issues of cultural identity and global understanding.